Discordance Between Eye-Specific Clinical Outcomes and Patient-Reported Visual Function After Faricimab Treatment for Neovascular Age-Related Macular Degeneration: A Two-Case Report - Tereza Pařilová; Libor Hejsek; Lenka Hodačová (Vision, 2026)
Neovascular age-related macular degeneration is a retinal disease of older adults causing central vision loss associated with macular neovascularization. Treatment response is commonly evaluated using visual acuity and retinal morphology. These measures may not fully reflect patient-perceived benefit. We report two older adults with neovascular age-related macular degeneration treated with faricimab who demonstrated discordance between clinical and patient-reported outcomes. In the first case, best-corrected visual acuity changed from 20/200 to 20/180 and central retinal thickness decreased from 480 to 389 µm, whereas the National Eye Institute Visual Function Questionnaire–25 score increased from 33.87 to 60.99 and the exploratory ordinal colour-vividness rating was 25 at baseline and 100 at follow-up. In the second case, best-corrected visual acuity improved from 20/100 to 20/45 and central retinal thickness decreased from 341 to 186 µm, whereas the National Eye Institute Visual Function Questionnaire–25 score declined from 67.08 to 33.17 and the exploratory ordinal colour-vividness rating was 75 at baseline and 25 at follow-up. Changes in patient-reported visual functioning may not always parallel conventional clinical outcomes, while the contrasting exploratory colour-vividness ratings observed in these two cases warrant further investigation.